2020
DOI: 10.1155/2020/8833757
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contaminants and Antibiogram of Ghana Paper Currency Notes in Circulation and Their Associated Health Risks in Asante-Mampong, Ghana

Abstract: Transmission of pathogens through currency notes has become very relevant in today’s world due to COVID-19 pandemic. This study profiled microbial flora and their antibiotic activities from Ghana paper currency (GH¢) notes in circulation in Mampong Municipal of Ashanti Region, Ghana. The study employed a cross-sectional design to assess bacterial contaminants and their antibiotic activities from January to May 2019. A total of 70 GH¢ notes consisting of 15 each of GH¢1, GH¢2, and GH¢5; 10 each of GH¢10 and GH¢… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 48 publications
5
11
2
1
Order By: Relevance
“…In previous studies, different types of bacteria in different currency notes were detected, [31][32][33][34][35][36][37][38][39][40] and, to best of our knowledge, the current study is the first to report the detection of A. radioresistens in Sudanese banknotes. Therefore, strategies and measures necessary to protect the currency handlers such as washable plastic currency and other preventive measures might be required.…”
Section: Resultsmentioning
confidence: 67%
“…In previous studies, different types of bacteria in different currency notes were detected, [31][32][33][34][35][36][37][38][39][40] and, to best of our knowledge, the current study is the first to report the detection of A. radioresistens in Sudanese banknotes. Therefore, strategies and measures necessary to protect the currency handlers such as washable plastic currency and other preventive measures might be required.…”
Section: Resultsmentioning
confidence: 67%
“…The growth of bacteria on Blood and MacConkey Agar were sub-cultured onto Nutrient Agar (Oxoid) and MacConkey Agar respectively to obtain pure isolates. The subculture plates were incubated for 12 to 24 hours at 37 o C. Standard microbiological methods were used to examine each isolate previously described [13].…”
Section: Culture and Morphological Characteristicsmentioning
confidence: 99%
“…Pure colonies were subjected to biochemical tests as previously described [13]. For Grampositive cocci, catalase and coagulase tests were performed to distinguish Streptococci from Staphylococci Coagulase test was carried out to differentiate Coagulase Negative Staphylococcus (CONS) such as Staphylococcus epidermidis from Staphylococcus aureus (positive).…”
Section: Biochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly described pathogenic bacterial genera are Escherichia (E. coli), Klebsiella, Staphylococcus, Enterococcus, Salmonella, Shigella, Pseudomonas, and Proteus [7,[14][15][16]. In recent literature, several studies have also explored the potential of antibiotic-resistant strains transmission via the currency notes [7,10,13,14,[16][17][18][19][20]. Most of these studies have reported the presence of pathogens-causing foodborne illnesses.…”
Section: Introductionmentioning
confidence: 99%